MMP2 and MMP9 in immature endothelial cells following surgical injury of rat cerebral cortex - a preliminary study - Frontczak-Baniewicz, Małgorzata; Walski, Michał; Madejska, Grażyna; Sulejczak, Dorota (Folia Neuropathologica, 2009)
Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases capable of extracellular matrix remodeling. They have been implicated in various physiological and pathological phenomena involving neurovascular unit elements (neurons, astrocytes and capillary vessels). Surgical injury of the fronto-temporal region of rat cerebral cortex induces massive neurodegeneration and cell death accompanied by astrogliosis. In the area adjacent to the damage, the induction of angiogenesis is observed, in which process immature endothelial cells are important players. The aim of this study was to examine the expression of MMP2 and MMP9 in cortical blood vessels following the surgical injury of cerebral cortex in the rat. Our data demonstrated absence of immature endothelial cells and lack of or only weak MMP2 and MMP9 immunoreactivities in some cortical capillaries in intact rats. Following the surgery, we found high MMPs’ immunoreactivities in walls of the vessels located in the cortex adjacent to the lesion site, and particularly in the immature endothelial cells. These results show for the first time the presence of MMPs in the immature (progenitor?) endothelial cells following surgical brain injury.